The Significance of Audio-Visual Aids in Teaching of English Vocabulary - Chiekezie, Patricia N; Inyang, Mayen-Julia Paul (GNOSI: An Interdisciplinary Journal of Human Theory and Praxis, 2021)
The traditional way to teach English in schools is based on the grammar structure of the sentences that are focused on the writing and reading skills which are not enough for the learning process of English as a Second Language since the other two macro-skills which are listening and speaking are important as well. Most of the time when learning a language and speaking is not emphasized as it should be; students are afraid to make mistakes in their oral presentations, and many of them would have difficulties speaking English. If this problem was taken into account from the beginning of their learning process, the students would have more confidence when speaking because they would be more engaged in the classroom. This problem is presented in all ages, therefore, it is important to use different kinds of material in the learning process, but always taking into consideration the level and age of students. The present study is aimed at showing the significance of audio-visual aids in the teaching of English vocabulary. The research shows that audio-visual materials are of incredible help in fortifying and encouraging the learning of a foreign language. This research concludes that the facilitator’s uses of audio-visual aids during the development of the English class are effective for learners as it allows them to be engaged, communicate, interact, and share during the English class.